Challenges of Public Credit Guarantee Schemes in Latin America during the Pandemic - Rudolph, Heinz P. (World Bank, Washington, DC, 2022)
Partial credit guarantees have been a central tool in countries’ strategies to support firms through the COVID-19 pandemic. This paper presents the results of a set of surveys covering 19 partial credit guarantees in 12 countries in the Latin America region, which were repeated at different stages of the pandemic crisis. The paper finds that most partial credit guarantees in the region are not large enough to foster change in the way the local financial sectors conduct business, how they engage with small and medium-size enterprises, and how they assimilate climate and gender considerations. Moreover, the response to the pandemic shows that most partial credit guarantees in the region have made limited use of the toolkit of parametric changes for boosting participation among financial institutions. Finally, the paper stresses the need for fair pricing methodologies and risk-based capital adequacy that may ensure the long-term sustainability of partial credit guarantee schemes.